2015
DOI: 10.22439/jba.v4i2.4895
|View full text |Cite
|
Sign up to set email alerts
|

Producing “global” corporate subjects in post-Mao China: Management consultancy, culture and corporate social responsibility

Abstract: China's rampant economic modernization-much discussed,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In the case of Haier, a Chinese multinational home appliances and consumer electronics company, its corporate culture started to emphasise customer needs and quality control for its business success in the market (Hawes, 2012). From an anthropological point of view, work organisations inevitably embrace national and regional cultures (Batteau, 2000;Chong, 2015; for a classical ethnographic study in Japan, see Kondo, 1987). Rather than simply replicating western management techniques of corporate culture building, traditional Chinese culture and the socialist heritage have provided two crucial intellectual resources for constructing corporate cultures in the Chinese context.…”
Section: Corporate Culture With Chinese Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Haier, a Chinese multinational home appliances and consumer electronics company, its corporate culture started to emphasise customer needs and quality control for its business success in the market (Hawes, 2012). From an anthropological point of view, work organisations inevitably embrace national and regional cultures (Batteau, 2000;Chong, 2015; for a classical ethnographic study in Japan, see Kondo, 1987). Rather than simply replicating western management techniques of corporate culture building, traditional Chinese culture and the socialist heritage have provided two crucial intellectual resources for constructing corporate cultures in the Chinese context.…”
Section: Corporate Culture With Chinese Characteristicsmentioning
confidence: 99%
“…The Chinese jianku fendou mentality was used to encourage the employees to ‘eat bitterness’ ( Chiku ), and nationalism to encourage them to work as ‘corporate soldiers’, though not necessarily emphasising monetary rewards or self-interest. Facing the cultural differences and conflicts between western and Chinese management styles, international firms need to develop a ‘signified corporate culture’ that suits the changing business culture and social milieu in post-Mao China (Chan et al, 2005; for an unsuccessful case, see Chong, 2015). Davies (2007) has shown that the successful localisation of Wal-Mart corporate culture in China relies on linking the Wal-Mart pursuit of success to Mao Zedong Thought and presenting its culture as a comprehensive way of life that unites workers’ work performance with personal and social morality, just like the socialist era work unit ( Danwei ).…”
Section: Corporate Culture With Chinese Characteristicsmentioning
confidence: 99%